An injectable double network hydrogel with hemostasis and antibacterial activity for promoting multidrug-resistant bacteria infected wound healing. (18th May 2022) - Zhang, Zibo; Guo, Jiadong; He, Yuxiang; Han, Jinzhi; Chen, Mingmao; Zheng, Yunquan; Zhang, Shenghang; Guo, Shaobin; Shi, Xianai; Yang, Jianmin
Abstract : A double network hydrogel with injectability, hemostasis, and antibacterial activity was developed through dynamic Schiff-base chemistry and photopolymerization crosslinking. It can enhance MRSA-infected full-thickness skin defect wound healing. Abstract : Multidrug-resistant bacteria infections frequently occur in wound care due to the excessive use of antibiotics. It can cause scar formation, wound closure delay, multiple organ failure, and high mortality. Here, a double network hydrogel with injectability, hemostasis, and antibacterial activity was developed to prompt multidrug-resistant bacteria infected wound healing. The double network hydrogel is composed of gelatin methacryloyl (GelMA), oxidized dextran (ODex), ε-polylysine (EPL), and bacitracin, and formed through the Schiff-base and UV-initiated crosslinking reaction. The injectable hydrogel with an adhesion effect could adapt to the irregular shape of the wound and possesses good hemostatic ability. The hydrogel presents good flexibility and rapid resilience due to its double network structure, and it can prompt cell proliferation and migration. In particular, the hydrogel has broad-spectrum in vitro antimicrobial activities against S. aureus, E. coli, and methicillin-resistant S. aureus (MRSA), and disrupts E. coli and MRSA biofilms. In vivo results demonstrated that the hydrogel can completely heal MRSA-infected wound in rats within 15 days, through inhibiting the growth of bacteria, accelerating skin tissue reepithelialization, collagen deposition, and angiogenesis, as well as adjusting the expression of CD31, α-SMA, and TNF-α. The findings of this study suggest that the presented hydrogel could enhance multidrug-resistant bacteria infected wound healing and mitigate antimicrobial resistance.